Spectro-timing analysis of MAXI J1535–571 using AstroSat. Issue 1 (28th June 2019) - Bhargava, Yash; Belloni, Tomaso; Bhattacharya, Dipankar; Misra, Ranjeev
Abstract: We report the results of the analysis of an AstroSat observation of the black hole candidate MAXI J1535–571 during its hard-intermediate state. We studied the evolution of the spectral and timing parameters of the source during the observation. The observation covered a period of ∼5 d and consisted of 66 continuous segments, corresponding to individual spacecraft orbits. Each segment was analysed independently. The source count rate increased roughly linearly by ∼30 per cent. We modelled the spectra as a combination of radiation from a thermal disc component and a power law. The timing analysis revealed the presence of strong quasi-periodic oscillations with centroid frequency νQPO fluctuating in the range of 1.7–3.0 Hz. We found a tight correlation between the QPO centroid frequency νQPO and the power-law spectral index Γ, while νQPO appeared not to be correlated with the linearly increasing flux itself. We discuss the implications of these results on physical models of accretion.